Combating Ponzi Schemes An in-Depth Look at Law Enforcement Effectiveness in Indonesian Context - Rizaldy Anggriawan (PÁZMÁNY LAW REVIEW, 2024)
Ponzi schemes, infamous for their ability to exploit unsuspecting investors, continue to pose a significant challenge to financial authorities globally. Indonesia, with a burgeoning economy and a growing financial sector, is not immune to the threat of fraudulent activities. This study delves into the effectiveness of existing law enforcement measures in Indonesia to combat Ponzi schemes, shedding light on areas that need of needing improvement. The research employs a mixed-methods research design, the study combines quantitative and qualitative data to comprehensively examine the issue. The findings reveal that while Indonesia has specific legal provisions to prosecute Ponzi scheme operators based on the sectoral laws and regulations, law enforcement still faces challenges related to evidentiary factors, witness factors, legal instrument, and limited resources. The reluctance of victims to report these schemes hinder successful prosecution. Law enforcement agencies often prioritize other criminal offenses due to resource constraints. To address these challenges, the study emphasizes the need for enhanced collaboration among law enforcement agencies and banking institutions, and the allocation of resources for these cases should be reconsidered. These reforms are essential to improve the state of law enforcement and protect potential victims of Ponzi schemes in Indonesia.